Exploration and Realization about Teaching Experimental of CNC Machine Tool Based on Virtual Simulation Technology - Liu, Lifu; Li, Wei; Chen, Xuerui (Manufacturing Technology Journal, 2023)
In order to cultivate students' professional skills and enhance students' practical ability, this paper proposes to create a virtual simulation experiment system of NC machine tool based on SolidWorks software platform, taking vertical machining center as the research object, which is integrated by three modules of NC machine tool structure, machine tool operation and machine tool processing. Firstly, the detailed assembly relationship of each subsystem of the machine tool, the assembly rela-tionship of the overall equipment and the system composition are displayed intuitively by 3D modeling, so that students can understand the 3D modeling method and structure composition of complex CNC machine tools. Secondly, according to the machining process characteristics of vertical machining center, using typical parts to create the virtual simulation platform to carry out complex parts programming and machining methods and steps based on vertical machining center. Through the full combination of virtual simulation experiment and actual equipment, it has significant results in improving students' interest in learning, ensuring teaching effect, reducing material waste, avoiding machine tool accidents and so on. And combined with the actual processing, operation of CNC machine tool experiment to achieve the combination of virtual and real, vivid image, rigorous and realistic, open and sharing, expand the numerical control technology class teaching and talent training. It also provides a good reference for similar curriculum development.
Keywords: Virtual simulation; Numerical control training; Design of experiment; Simulation platform